Konstantin Stanislavski and Michael Chekhov: tracing the two practitioners' "lures" for emotional activation. Issue 1 (2nd January 2021) - Evangelatou, Aphrodite
ABSTRACT: Konstantin Stanislavski points out that emotions are like wild animals that can only be lured rather than approached directly; he urges his students not to try to force emotions to arrive, as feelings are independent of the will and cannot be manipulated. Like a whisperer, the actor should lure emotions, gently invite them in, approach them indirectly, instead of "going after" them and scaring them away. During his extensive and revolutionary research on the actor's craft, the Russian pioneer discovered various such indirect "lures" for emotional activation. This article reviews the tangible points of entry to the unruly feelings as identified by Stanislavski, as well as those explored by his pupil, Michael Chekhov. The two practitioners' approach to emotion is examined here, with emphasis on two key publications respectively: Stanislavski's An Actor's Work and Chekhov's To the Actor . The article discusses the lures of concentration, imagination, "well-founded, apt and productive" actions, emotion memory, tempo-rhythm, empathy (fellow-feeling), external stimuli such as lighting and props, and the actor's focus on that which is specific, tangible, and detailed. The review of Stanislavski's lures is followed by a discussion of Michael Chekhov's insights on artistically-induced emotion and the pathways he identified for stirring the performer's inner life, emphasizing the exploration of qualities of movement, objective atmospheres, and the actor's embodied imagination.